The Neurolaw Perspective on Criminal Responsibility of Children in Indonesia - Rahmawati, Aulia; Isnaeni, Shifaniya; Hilda Laela, Cahya; Asmara, Teddy; Waluyadi, Waluyadi (Syntax Corporation, 2025)
This study examines the relevance of the neurolaw approach in the juvenile justice system in Indonesia. Neurolaw combines neuroscience and law to understand the relationship between children's brain development and criminal responsibility. The focus of the research is the juvenile justice system regulated under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which primarily emphasizes biological age without considering neurological aspects. The research method employed is a normative juridical approach with legislative and neuroscience perspectives. The findings indicate that the juvenile justice system in Indonesia has not fully accommodated children's neurological development, thereby posing a risk of imposing punishments that are not aligned with the child's condition. This study recommends revising the Juvenile Criminal Justice System Law to incorporate neurocognitive evaluations in the judicial process to create a more accurate and evidence-based system